Valoração de resíduos agroindustriais para produção de biomassa microalgal e aplicação na agricultura - Braun, Julia Catiane Arenhart (2024)
Global population growth brings the need to increase crop yields for food production. Conventional agricultural management is based on the application of chemical fertilizers. Increasing these fertilizers to achieve higher yields can pose problems for soil health and the environment. Microalgae biostimulants emerge as an alternative to reduce these damages. These compounds can result in improved plant development and increased productivity. However, large-scale microalgae biomass production can present challenges for bio-stimulant production. This is due to high production costs, primarily associated with growth media. The use of alternative methods for microalgae production, such as agro-industrial by-products, can bring greater savings to the production of this bioinput. The objective was to use whey in microalgae cultivation to increase biomass and subsequently develop a microalgal biostimulant. The three microalgae strains studied (Spirulina platensis, Chlorella homosphaera and Scenedesmus obliquus) showed tolerance to the addition of whey in fed-batch mode at low concentrations (1%, v/v). The raw whey was utilized by the microalgae in their metabolism, resulting in increased maximum specific growth rates and biomass concentration. Cost savings in growth media of up to 32%, 57%, and 73% were observed for the cultivation of S. obliquus, S. platensis, and C. homosphaera, respectively, when producing 1 kg of biomass in 0.5 L reactors. However, scaling up with natural light inhibited the growth of S. platensis in media with whey addition after 15 days, indicating the need for further studies with lower concentrations of the residue to reduce microalgal stress. The use of S. platensis biomass as a raw material for producing microalgal bio-stimulants showed bio-fertilizer potential (produced in 20% Zarrouk medium). Cell disruption of the microalgae by ultrasonic probe released bioactive compounds that can be used by plants in their metabolism, such as free amino acids and macro and micronutrients. Application of the bio-stimulant through seed treatment (ST) resulted in increased root area in the early stages of soybean, wheat, and oat seedlings. Soybean seed treatment with the developed bioproduct in an experimental field resulted in increased above-ground plant parts and number of nodules compared to chemical seed treatment alone. Seed treatment combined with foliar application in barley resulted in a positive influence on root and above-ground plant parts in treatments with microalgae compared to the control. Additionally, increased productivity was recorded in barley seed treatment compared to conventional field management. The application of dry S. platensis biomass in barley fields can serve as a partial substitute for chemical fertilizers, bringing greater sustainability to brewing barley producers without resulting in yield losses. Therefore, the use of whey in microalgae cultivation can increase microalgal biomass production. Additionally, the biostimulants and biofertilizers produced from S. platensis microalgal biomass have shown potential for agricultural application, potentially making crop cultivation more profitable and sustainable.